(3GdZQQ GdHgjI aj TQM GdNRQLjIs - (3Hf MSjf Hf YHO Gdedc GdTGaYjs; (3YHO Gddg Hf eMeO GdNRQLj, VjGA GdOjf CHh eMeO,J (B626 (3g` s
(3ChdgG (B:s
(3hHYO agPg ahGFO hajg HMQ GdNRQLjI fXe GdTjN VjGA GdOjf CHj eMeO YHOGddg Hf eMeO GdNRQLj dNUJgG ef TQM GdTjN GdYdGeI eMeO Hf CHj HcQ GdOeGejfj s
(3BNQgG (B:s
(3hEfeG hVYgG ddeJhSW aj gPG GdYde bO Je gPG GdTQM GdeHQc HMeOGddg hYhfg hMSf Jhajbg hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B124 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B117 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B460s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdYQhV hGdbhGais